2014
DOI: 10.18632/oncotarget.1769
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a long non-coding RNA as a novel biomarker and potential therapeutic target for metastatic prostate cancer

Abstract: Metastatic prostate cancer (PCa) is still an incurable disease. Long non-coding RNAs (lncRNAs) may be an overlooked source of cancer biomarkers and therapeutic targets. We therefore performed RNA sequencing on paired metastatic/non-metastatic PCa xenografts derived from clinical specimens. The most highly up-regulated transcript was LOC728606, a lncRNA now designated PCAT18. PCAT18 is specifically expressed in the prostate compared to 11 other normal tissues (p<0.05) and up-regulated in PCa compared to 15 othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
165
1
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 205 publications
(170 citation statements)
references
References 38 publications
1
165
1
3
Order By: Relevance
“…Twenty milliliter of EDTA-anticoagulated bone marrow was used for total RNA extraction after buffy coat preparation. Bone marrow was employed for cytogenetic analysis, as stated by the international guidelines [16], and for PcG expression analysis. Concomitantly, 20 ml of peripheral blood was employed for RNA extraction, banking and for analysis of the BCR-ABL1/ABL1 International Scale (IS) ratio by the GeneXpert Technology (Cepheid, Maurent-Scopont, France) after 3 and 6 months of therapy, as indicated by European guidelines [17].…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty milliliter of EDTA-anticoagulated bone marrow was used for total RNA extraction after buffy coat preparation. Bone marrow was employed for cytogenetic analysis, as stated by the international guidelines [16], and for PcG expression analysis. Concomitantly, 20 ml of peripheral blood was employed for RNA extraction, banking and for analysis of the BCR-ABL1/ABL1 International Scale (IS) ratio by the GeneXpert Technology (Cepheid, Maurent-Scopont, France) after 3 and 6 months of therapy, as indicated by European guidelines [17].…”
Section: Patientsmentioning
confidence: 99%
“…Gene-expression levels of PRC1 components were assayed using reverse transcribed cDNA and SYBR green primers following a previously described procedure for amplification and relative gene-expression quantification [16]. GAPDH was used as a reference gene.…”
Section: Quantitative Pcrmentioning
confidence: 99%
“…Relative gene expression level was quantified based on the cycle threshold (Ct) values, where GAPDH was used as an internal control whose expression was stable in primary and metastatic PC 10 . For quantitative results, expression of each gene was represented as a fold change using the following mathematical model: …”
Section: Real-time Pcrmentioning
confidence: 99%
“…The lncRNA metastasis-associated lung adenocarcinoma transcript 1 (MALAT1) was another marker of PC, the expression of which was correlated with poor prognosis in PC patients 9 . Crea et al found a total of 153 upregulated and 77 downregulated lncRNAs in metastatic versus nonmetastatic xenografts and focused on PCAT18 for biomarker analysis 10 . Based on the expression profiles, we investigated the expression pattern of the 10 most dysregulated lncRNAs in our blood samples of PC patients and normal controls, and found PCGEM1 could serve as a new diagnosis marker for metastatic prostate cancer for AJCC for the following reasons: (1) the expression of PCGEM1 was higher in metastatic group than that in localized and control groups (p < 0.001); (2) PC patients with higher AJCC stage had significantly elevated PCGEM1 expression (p < 0.001); (3) PC patients with lower PCGEM1 showed prolonged survival time.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, PCAT18 was found to be detectable in plasma samples with levels that increased incrementally from healthy individuals to those with localized and metastatic PCa. Through RNA sequencing of paired metastatic/nonmetastatic PCa xenografts, PCAT18 was identified as a potential biomarker for metastatic PCa [13].…”
mentioning
confidence: 99%